Hubungan Cita Rasa dan Variasi Menu Makanan dengan Sisa Makanan pada Santriwati di Pondok Pesantren An-Nashar Kota Batam - Herda Awaliyah; Siska Pratiwi; Inke Asmika (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Food waste is food left on the plate after consumption and reflects an individual's ability and desire to finish food. In Islamic boarding schools, this problem often arises because the taste of the food is less favorable and the menu variety is limited. This research aims to determine the relationship between taste and menu variations and food waste among female students at the An-Nashar Islamic Boarding School, Batam City.This research used a cross sectional analytical design with 46 respondents selected using simple random sampling. Data were collected through self-reported consumption using the comstock method, analyzed using the Chi-Square test. The results showed that the majority of female students who rated the taste and menu variety as poor tended to leave food behind, but the p-value for taste was 0.989 and menu variety was 0.650 (>0.05), so there was no significant relationship. Inconclusion, there is no significant relationship between taste or menu variety and food waste.